2015
DOI: 10.1002/marc.201500388
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Loading Efficiency between Hyperbranched Polymers and Cross‐Linked Nanogels at Various Branching Densities

Abstract: The effect of branching point structures and densities is studied between azido-containing hyperbranched polymers and cross-linked nanogels on their loading efficiency of alkynyl-containing dendron molecules. Hyperbranched polymers that contained "T"-shaped branching linkage from which three chains radiated out and cross-linked nanogels that contained "X"-shaped branching linkage with four radiating chains are synthesized in microemulsion using either atom transfer radical polymerization (ATRP) or conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…It is also important to note that the leak of deactivator into aqueous phase could also affect the radical–radical termination reaction that cannot be completely avoided in any radical polymerization. The radical coupling reaction between two propagating primary chains produced a tetrafunctional cross‐linkage, so called “X”‐shape cross‐linkage, [ 74 ] from which four chains radiate out. This “X”‐cross‐linkage was not included in the DB calculation, but indeed had influence on the structural compactness of the hyperbranched polymers.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that the leak of deactivator into aqueous phase could also affect the radical–radical termination reaction that cannot be completely avoided in any radical polymerization. The radical coupling reaction between two propagating primary chains produced a tetrafunctional cross‐linkage, so called “X”‐shape cross‐linkage, [ 74 ] from which four chains radiate out. This “X”‐cross‐linkage was not included in the DB calculation, but indeed had influence on the structural compactness of the hyperbranched polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Gao et al. have demonstrated that the loading efficiencies of HBPs were three times larger than that in the cross‐linked nanogel system achieved through copper‐catalyzed click reaction between azido groups in the HBPs or cross‐linked structures and alkynyl‐containing dendron guest molecules . They also used a structurally defined LCHBP grafting star polymer to encapsulate Au 25 (SR) 18 nanoclusters for polymer‐Au nanocomposite catalysis ( Figure ) .…”
Section: Applications Of Lchbpsmentioning
confidence: 99%
“…[11,17,18] Gao et al have demonstrated that the loading efficiencies of HBPs were three times larger than that in the cross-linked nanogel system achieved through copper-catalyzed click reaction between azido groups in the HBPs or cross-linked structures and alkynyl-containing dendron guest molecules. [155] They also used a structurally defined LCHBP grafting star poly mer to encapsulate Au 25 (SR) 18 nanoclusters for polymer-Au nanocomposite catalysis (Figure 26). [105] The LCHBP was synthesized by the developed polymerization in microemulsion of an inimer with a cyclic disulfide-containing methacrylate monomer, and subsequent radiating polymerization for growing arms.…”
Section: Catalyst Carriermentioning
confidence: 99%
“…Copper partitioning between the dispersed phase to the continuous phase has been critical to impact the control of ATRP in emulsion systems . Although a highly hydrophobic ligand BPMODA* was used in the present study, the copper complex, especially the Cu(II)/BPMODA* was still possible to exit the dispersed polymer latex, resulting in a slower radical deactivation reaction and longer primary chain length than expected.…”
Section: Resultsmentioning
confidence: 94%
“…Among the various synthetic methods, radical‐based self‐condensing vinyl polymerization (SCVP) of inimers (containing ini tiator fragment and mono mer vinyl group in one molecule) and/or transmers (containing chain trans fer group and mono mer vinyl group in one molecule) has become particularly popularly in the past two decades. All established reversible deactivation radical polymerizations (RDRP) techniques, including atom transfer radical polymerization (ATRP), nitroxide‐mediated polymerization (NMP) and reversible addition–fragmentation chain transfer (RAFT) polymerization have been intensively applied in the (co)polymerization of inimers and transmers, primarily in solution, for synthesis of branched polymers with various compositions. For instance, those synthesized by ATRP possess high density of chain‐end initiating groups and are easy to extend with vinyl monomers using the same technique .…”
Section: Introductionmentioning
confidence: 99%